PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) BERBANTUAN MEDIA EDUCAPLAY UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA SMKS SETIA BUDI BINJAI - Aulia Rusli, Cindy; Thohiri, Roza; Ramdhansyah; Aida Silalahi, Sondang; Nurhayani, Ulfa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to increase student activities and learning outcomes through the implementation of the Project Based Learning (PjBL) learning model assisted by Educaplay media. This Class Action Research (PTK) was carried out in two cycles on 16 students of class X AKL SMKS Setia Budi Binjai. Research results show that the implementation of PjBL with the help of Educaplay is effective in increasing student activity and learning outcomes. The average score of students increased from 68.2 in the pre-test to 75.8 in Cycle I and 86.7 in Cycle II, while the classical learning completion increased from 50% to 62.5% and reached about 90% in Cycle II. Student learning activities also reached the very good category in Cycle II. Thus, PjBL with the help of Educaplay can be an effective learning alternative in increasing student activities and learning outcomes.